Government initiative and policies on water conservation and wastewater treatment in Brazil - Abessa, Denis Moledo de Souza [UNESP]; Ambrozevicius, Andrea Pimenta (Elsevier, 2020)
This chapter aims to describe the water management and conservation in Brazil and show how the public policies evolved along time. It starts by presenting the geographical context and the main hydrographic basins of the country, with their respective characteristics. Then, it presents the historical and legal framework of the water management in the country, addressing the evolution of actions and public policies. Next, the chapter describes the National Policy of Water Resources (PNRH), with the respective tools for water resources management and the institutional adjustments required to allow the policy implementation, such as the creation of the National Water Agency. By the end of the chapter, some additional initiatives taken by the public power to improve the PNRH effectiveness are discussed, and the perspectives for the future are presented.
Keywords: Brazilian hydrographic basins; Brazilian Policy on Water Resources; water management tools; water resources management